Halo formation and emittance growth in the transport of spherically symmetric mismatched bunched beam - Silva, Thales Marques Corrêa da (2015)
The effect of an initial envelope mismatch on the transport of bunched spherically symmetric beams is investigated. A particle-core model is used to estimate the maximum radius that halo particles can reach. The theory is used to obtain an empirical formula that provides the halo size as a function of system parameters. Taking into account, the incompressibility property of the Vlasov dynamics and the resulting Landau damping, an explicit form for the final stationary distribution attained by the beam is proposed. The distribution is fully self-consistent, presenting no free fitting parameters. The theory is used to predict the relevant beam transport properties, such as the final particle density distribution, the emittance growth, and the fraction of particles that will be expelled to form halo. The theoretical results are compared to the explicit N-particle dynamics simulations, showing a good agreement.